Case Report: Second-Degree Burns due to Hot Liquid Asphalt Cement Spillage in an Adult Patient with Comorbid Diabetes Mellitus - Maha Umami Putri Qulzum; Sri Vitayani; Widjoyo (The International Journal of Medical Science and Health Research, 2025)
Burns represent a significant form of injury that leads to substantial tissue damage, necessitating complex management strategies tailored to the degree and total body surface area (TBSA) affected. The complexity of burn management is notably increased in patients with comorbidities such as diabetes mellitus. Diabetes mellitus can induce vascular disorders and peripheral neuropathy, which collectively impair the natural wound healing process. This report details the case of a 42-year-old male who presented to the Emergency Department of Makassar City Hospital with burns on his right and left legs. The injuries were sustained approximately 30 minutes prior from a spill of hot liquid asphalt cement at his workplace and were accompanied by a significant burning sensation. The patient, weighing 58 kg, reported no fever, headache, dyspnea, nausea, or vomiting, with normal bowel and bladder function. He had no history of similar injuries, allergies, or hypertension. However, he had a known history of diabetes mellitus, which was managed with metformin 500 mg three times daily. A family history of diabetes was present on his maternal side. Burns, or combustio, are defined as tissue damage or loss resulting from contact with thermal sources like fire and hot water, or with chemicals, electricity, and radiation. Hot water and flames are the most frequent causes of burns. The primary principle of first aid is to halt the burning process and reduce the wound's temperature. For flame-related burns, this involves the "Stop, Drop, Cover (Face) & Roll" technique.